Law and the contradictions of the disability rights movement - Bagenstos, Samuel R. (New Haven, Conn. ; London : Yale University Press, 2009)
The passage of the Americans with Disabilities Act in 1990 was hailed as revolutionary legislation, but in the ensuing years restrictive Supreme Court decisions have prompted accusations that the Court has betrayed the disability rights movement. Here, the author examines the history of the movement.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: People with disabilities -- Legal status, laws, etc. -- United States; Discrimination against people with disabilities -- Law and legislation -- United States; People with disabilities -- Civil rights -- United States; Law; Disability & the law